2010
DOI: 10.1162/jocn.2009.21334
|View full text |Cite
|
Sign up to set email alerts
|

Neural Mechanisms of Verb Argument Structure Processing in Agrammatic Aphasic and Healthy Age-matched Listeners

Abstract: Processing of lexical verbs involves automatic access to argument structure entries entailed within the verb's representation. Recent neuroimaging studies with young normal listeners suggest that this involves bilateral posterior perisylvian tissue, with graded activation in these regions based on argument structure complexity. The aim of the present study was to examine the neural mechanisms of verb processing using functional magnetic resonance imaging (fMRI) in older normal volunteers and patients with stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
68
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(83 citation statements)
references
References 79 publications
15
68
0
Order By: Relevance
“…In one study (Thompson et al, 2007), they observed greater neural activity in the left supramarginal and angular gyri for transitive relative to intransitive verbs. In a follow-up study (Thompson et al, 2010) using the same task and materials, they observed similar results but this time restricted to the angular gyrus. In a different study, Meltzer-Asscher, Schuchard, den Ouden, and Thomphon (2013) observed greater neural activity in the bilateral angular and supramarginal gyri, as well as in the right posterior superior temporal gyrus (STG), the right MTG, and the right middle and superior frontal gyri for verbs that can act as transitive or intransitive versus verbs that must exclusively act as intransitive.…”
Section: Introductionmentioning
confidence: 58%
“…In one study (Thompson et al, 2007), they observed greater neural activity in the left supramarginal and angular gyri for transitive relative to intransitive verbs. In a follow-up study (Thompson et al, 2010) using the same task and materials, they observed similar results but this time restricted to the angular gyrus. In a different study, Meltzer-Asscher, Schuchard, den Ouden, and Thomphon (2013) observed greater neural activity in the bilateral angular and supramarginal gyri, as well as in the right posterior superior temporal gyrus (STG), the right MTG, and the right middle and superior frontal gyri for verbs that can act as transitive or intransitive versus verbs that must exclusively act as intransitive.…”
Section: Introductionmentioning
confidence: 58%
“…There is evidence from normal speakers that comprehension of a verb activates not only lexical semantics but also argument structure knowledge (Thompson, Bonakdarpour, & Fix, 2010).…”
Section: Future Research Directionsmentioning
confidence: 99%
“…Hence, affected regions of the brain can remain active during language task performance [52]. Nevertheless, in general, PPA-G and StrAg are associated with necrosed or atrophied tissue in the left frontal region, although tissue atrophy in PPA-G also may involve the temporo-parietal junction (TPJ) and lesions in StrAg can include both anterior and posterior perisylvian brain regions [44,56,65]. Conversely, PPA-L and StrAn typically result from compromised tissue in the temporo-parietal region.…”
Section: Introductionmentioning
confidence: 99%